WAKAF UANG SEBAGAI INSTRUMEN SISTEM EKONOMI ISLAM YANG BERKEADILAN (ZISWAF: Jurnal Zakat dan Wakaf, 2015)
During this wakaf has always identified with the Waqf land, but as the birth of Act No. 41 of 2004 about the endowments, has made the concept of Waqf contains a very broad dimension that includes not only the treasure does not move but also the treasure moves, i.e. including the Waqf money which their use is very extensive is not limited to the establishment of places of worship and social kegamaan. The presence of this legislation is projected as a means of social engineering, doing changes mind, attitude and behaviour of the Muslims as well as to empower of Waqf which is one instrument in building socio-economic life of the Muslims. Beside that, also as momentum permberdayaan wakaf productively in accordance with the Islamic Shari’ah breath.